1999
DOI: 10.1021/bi9900976
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Dynamics of Partially Folded Actin

Abstract: Steady-state and time-resolved intrinsic fluorescence, fluorescence quenching by acrylamide, and surface testing by hydrophobic label ANS were used to study the structure of inactivated alpha-actin. The results are discussed together with that of earlier experiments on sedimentation, anisotropy of fluorescence, and CD spectrum in the near- and far-UV regions. A dramatic increase in ANS binding to inactivated actin in comparison with native and unfolded protein indicates that the inactivated actin has solvent-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 47 publications
(72 reference statements)
5
76
0
1
Order By: Relevance
“…In this state, the tryptophan residues are located in a more polar and mobile environments. It was described that the form and position of the fluorescence spectrum of inactivated actin are independent of the solution ionic strength, the presence of reducing agents, the excessive quantity of ATP and Ca 2+ , the protein concentration and the way of the inactivation [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this state, the tryptophan residues are located in a more polar and mobile environments. It was described that the form and position of the fluorescence spectrum of inactivated actin are independent of the solution ionic strength, the presence of reducing agents, the excessive quantity of ATP and Ca 2+ , the protein concentration and the way of the inactivation [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the parameter A has a value of 2.6 and 1.4 in the absence or in the presence of 1300 μM decavanadate, respectively. According to Turoverov [28], inactivated actin has the parameter A = 1.30. Therefore, it is suggested that V 10 promotes actin inactivation in the concentration range used (0-1300 μM decavanadate).…”
Section: Changes In Actin Intrinsic Fluorescence Upon Vanadate Solutimentioning
confidence: 99%
“…[30] Fluorescence was excited at the long-wave absorption edge where the contribution of tyrosine residues is negligible. Fluorescence intensity was recorded at 320 and 365 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The endoribonuclease activity was measured as described in [2]. The proteasome peptidase activity was measured from the release of (7-amino)-4-methylcumarin using a custom-made fluorimeter [15].Proteasomes excreted into the c-medium and cellular proteasomes were characterized by comparison of their proteolytic activities. Three peptidase activities CELL BIOLOGY…”
mentioning
confidence: 99%
“…The endoribonuclease activity was measured as described in [2]. The proteasome peptidase activity was measured from the release of (7-amino)-4-methylcumarin using a custom-made fluorimeter [15].…”
mentioning
confidence: 99%